What to bring - Schultz Nicholson, Lorna (Owlkids Books, 2023)
"Malia is enjoying a summer day in her backyard when she glances at the sky -- and it looks very strange. A forest fire is sweeping into the area where she lives, and Malia soon learns that she and her family will have to evacuate their home. As they quickly get ready to leave, Malia's mother tells her to pack only what's important. At first, Malia struggles to decide what to take with her. She wants everything - and the "to bring" pile in her room grows and grows. But as the urgency and chaos swirl around her, Malia is able to come to an understanding of what is truly important and knows exactly what to bring with her."--